Spray losses study of two pesticides by UASS in integrated rice–crayfish farming system and acute toxicity evaluation on Procambarus clarkii - Liu, Yang; Wang, Guangyu; Li, Yuanyuan; Zhang, Zhenhua; Pang, Sen; He, Xiongkui; Song, Jianli (Frontiers in Plant Science, 2023)
While the integrated rice-crayfish (Procambarus clarkii) farming system (IRCFS) is widely developing in China, the widespread use of Unmanned Aerial Spraying Systems (UASS) to protect rice from pests has led to potential pesticide risk for the crayfish in IRCFS. Therefore, it is crucial to examine UASS's spray deposition and drift in IRCFS. In this study, we used the oligonucleotide sequence-tracking / dotblotting (OSTDB) method to trace pesticide spraying. We collected detailed data not only on spray loss in the paddy fields, but also on spray drift in the breeding ditches caused by upwind and downwind spray areas. Additionally, pesticide residues in the breeding ditches were measured using LC-MS/MS by collecting water samples after pesticide application. The data analysis indicated that the spray loss in the paddy field was significantly greater than that in the breeding ditches. The spray drift in the breeding ditches, caused by the upwind spray area, was seven times higher than that originating from the downwind spray area. Furthermore, the results also revealed that the bulk flow between the paddy fields and the breeding ditches contributed a substantial amount of pesticide residue to the water body in the breeding ditches. In addition, we investigated the acute toxicities of common insecticides using in paddy fields, including thiamethoxam (THI), chlorantraniliprole (CHI), THI• CHI-Mix and THI• CHI-WG. The results demonstrated that the spray losses and spray drift from UASS spray applications of these pesticides in IRCFS would not cause acute toxicity or death in crayfish. These findings provide important materials for establishing pesticide application standards and guiding the field testing of droplet deposition and drift in IRCFS. This is a provisional file, not the final typeset article al., 2018). During the rice-growing phase, the crayfish live harmoniously in the paddy fields that are connected to breeding ditches, and migrate back to these ditches during the field drying and rice harvesting periods (